2001
DOI: 10.1177/00131640121971527
|View full text |Cite
|
Sign up to set email alerts
|

Differential Item Functioning in the Wisc-III: Item Parameters for Boys and Girls in the National Standardization Sample

Abstract: The Wechsler Intelligence Scale for Children–Third Edition (WISC-III) is the most widely used test of intelligence in the world. However, the manual for the WISC-III provides insufficient detail regarding the detection of differential item functioning (DIF). The WISC-III national standardization sample ( N = 2,200) was used to investigate DIF in six WISC-III subtests. After fitting two parameter logistic and graded response models to the data, items were tested for DIF using the item response theory likelihood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
48
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 42 publications
0
48
0
Order By: Relevance
“…If any items show DIF, the items should be revised or eliminated after thoughtful evaluation by the selection committee or bias reviewers. It is important to note that even though a subtest shows almost equal numbers of DIF items for each group, say 6 items favoring one group and 7 items favoring the other group, the result can be consequential for examinees at the total test score (see Maller, 2001). This problem arises when a raw score difference between the focal group and the reference group in a subtest is accumulated in the total test score.…”
Section: Resultsmentioning
confidence: 99%
“…If any items show DIF, the items should be revised or eliminated after thoughtful evaluation by the selection committee or bias reviewers. It is important to note that even though a subtest shows almost equal numbers of DIF items for each group, say 6 items favoring one group and 7 items favoring the other group, the result can be consequential for examinees at the total test score (see Maller, 2001). This problem arises when a raw score difference between the focal group and the reference group in a subtest is accumulated in the total test score.…”
Section: Resultsmentioning
confidence: 99%
“…In Chapter 3 of Culture and Children's Intelligence it is asserted that there is no meaningful evidence of test bias among the Wechsler series tests and notes that two studies (Weiss, Prifitera, & Roid, 1993;Weiss & Prifitera, 1995) found the WISC-III to predict achievement equally well for African American, Hispanic American and White American children. It does not note that no published studies have investigated ethnicity related item level bias on the WISC-III or that the only existing published study of gender bias found numerous items that functioned differently for girls and boys (Maller, 2001).…”
mentioning
confidence: 95%
“…The WISC-III is composed of 13 subtests and provides summary estimates of general intelligence (Full Scale IQ) and verbal and performance (visuo-spatial and constructional) abilities, as well Transcultural Psychiatry 45 (4) as indices that measure verbal comprehension, perceptual organization, freedom from distractibility (working memory), and processing speed. The WISC-III and the most recent version of the Wechsler intelligence scales for children, the WISC-IV (Wechsler, 2003), are the most widely used and researched assessment tools of cognitive function in the world (e.g., Maller, 2001).…”
mentioning
confidence: 99%
“…Thus, the characteristics of 534 Language Testing 29(4) items identified as exhibiting DIF have been well documented (e.g. Abbott, 2007;Carlton & Harris, 1992;Chen & Henning, 1985;Elder, 1996;Kim, 2001;Lawrence & Curley, 1989;Maller, 1997Maller, , 2001Pae, 2004a;Ryan & Bachman, 1992;Sasaki, 1991;Takala & Kaftandjieva, 2000;Thissen, Steinberg, & Wainer, 1988). Notably, however, researchers have typically based such empirical studies on a cross-sectional research design, indicating that the presence of DIF was examined at a single point in time.…”
mentioning
confidence: 99%